2019
DOI: 10.1159/000495305
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Severe Chronic Upper-Airway Disease (SCUAD) in Patients with Allergic Rhinitis: A Real-Life Multicenter Cross-Sectional Italian Study

Abstract: Background: There are few studies regarding severe chronic upper-airway disease (SCUAD) that represents an important socioeconomic problem for the treatment of rhinitis and associated comorbidities, particularly asthma. Objectives: The aim of our study is to evaluate the prevalence of this pathology in patients with allergic rhinitis (AR) in real life, to phenotype allergic patients with SCUAD, and to identify which factors are related to the severity of the disease. Methods: We studied 113 patients with uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…A total of 4467 participants were assessed, with the mean reported age ranging between 15 and 55 years old. In four studies (eight reports), all the 2622 participants were reported to have AR, 36,37,41,43,44,48–50 while asthma was reported in all the 1245 participants in six studies (seven reports) 19,22,38–40,46,47 . Five studies included only patients ( n = 508) with both AR and asthma 17,20,35,42,45 …”
Section: Resultsmentioning
confidence: 99%
“…A total of 4467 participants were assessed, with the mean reported age ranging between 15 and 55 years old. In four studies (eight reports), all the 2622 participants were reported to have AR, 36,37,41,43,44,48–50 while asthma was reported in all the 1245 participants in six studies (seven reports) 19,22,38–40,46,47 . Five studies included only patients ( n = 508) with both AR and asthma 17,20,35,42,45 …”
Section: Resultsmentioning
confidence: 99%
“…Loratadine tablet is a tricyclic antihistamine with high efficiency and long-lasting effect, and it is a selective peripheral H1 receptor antagonist, which can relieve all kinds of symptoms caused by allergic reactions [ 24 ]. Antihistamines are available orally and intranasally.…”
Section: Discussionmentioning
confidence: 99%
“…Причинами могут являться как факторы, связанные с болезнью (тяжелое течение -SCUAD, сопутствующие заболевания), так и проблемы диагностики, а также приверженности к терапии [52]. Далеко не всем пациентам возможно провести АСИТ -такая терапия проводится не более, чем у 20% больных [21,53].…”
Section: выводыunclassified
“…В данной группе большинство пациентов имели полисенсибилизаацию (72%), а также характерную коморбидную патологию: БА (49%), назальный полипоз (30%), синусит (51%). Полисенсибилизация коррелировала со SCUAD, предположительно в связи с большей выраженностью воспалительного процесса [53]. По данным литературы, распространенность тяжелых неконтролируемых на стандартной терапии форм АР могут достигать 20% [21].…”
Section: выводыunclassified